2019
DOI: 10.3390/cells8101272
|View full text |Cite
|
Sign up to set email alerts
|

PTPN11 (SHP2) Is Indispensable for Growth Factors and Cytokine Signal Transduction During Bovine Oocyte Maturation and Blastocyst Development

Abstract: This study was aimed to investigate the role of SHP2 (Src-homology-2-containing phosphotyrosine phosphatase) in intricate signaling networks invoked by bovine oocyte to achieve maturation and blastocyst development. PTPN11 (Protein Tyrosine Phosphatase, non-receptor type 11) encoding protein SHP2, a positive transducer of RTKs (Receptor Tyrosine Kinases) and cytokine receptors, can play a significant role in bovine oocyte maturation and embryo development, but this phenomenon has not yet been explored. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 85 publications
0
53
0
Order By: Relevance
“…SHP2 showed nuclear localization in several reproductive tissues, like our previous study on in vitro oocyte maturation and one study regarding sperm maturation, which stated that SHP2 showed nuclear expression in germ cell-supporting cells (cumulus cells and sertoli cells); however, the function of nuclear-localized SHP2 still requires exploration in those tissues [17,28]. Ran et al found that nuclear-localized SHP2 in the uterus was essential for the estrogen receptor-α (ER-α) nuclear transcription of progesterone (pgr) gene in mice, and for the tissue (uterus)-specific SHP2 knockout to completely inhibit embryo implantation [32].…”
Section: Shp2 Nuclear Localization and Role In Transcriptionmentioning
confidence: 81%
See 3 more Smart Citations
“…SHP2 showed nuclear localization in several reproductive tissues, like our previous study on in vitro oocyte maturation and one study regarding sperm maturation, which stated that SHP2 showed nuclear expression in germ cell-supporting cells (cumulus cells and sertoli cells); however, the function of nuclear-localized SHP2 still requires exploration in those tissues [17,28]. Ran et al found that nuclear-localized SHP2 in the uterus was essential for the estrogen receptor-α (ER-α) nuclear transcription of progesterone (pgr) gene in mice, and for the tissue (uterus)-specific SHP2 knockout to completely inhibit embryo implantation [32].…”
Section: Shp2 Nuclear Localization and Role In Transcriptionmentioning
confidence: 81%
“…SHP2 plays a significant role in oocyte meiotic maturation by inhibiting mitochondrial degradation via enhancing mTOR dependent mitochondrial biogenesis and inhibiting mitophagy [52]. The inhibition of SHP2 with Phenyl hydrazono pyrazolone sulfonate 1 (PHPS1), which is an active site-directed inhibitor, also significantly reduced meiotic maturation [17]. One study stated that mitochondria localized SHP2 dephosphorylated and inhibited adenine nucleotide translocase 1 (ANT1), which is essential for the nucleotide-binding domain and leucine-rich repeat containing (NLRP3) localization in mitochondria, and this resulted in reactive oxygen species (ROS) induced apoptosis [53].…”
Section: Cytoplasmic Localized Shp2 Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting was performed as described previously, with some modification [ 30 , 31 ]. The protein concentrations were quantified by using a Bio-Rad Protein Assay Kit (Bio-Rad Laboratories, CA, USA).…”
Section: Methodsmentioning
confidence: 99%